2020
DOI: 10.3390/ma13143146
|View full text |Cite
|
Sign up to set email alerts
|

Quarry Waste as Precursors in Geopolymers for Civil Engineering Applications: A Decade in Review

Abstract: Carbon footprint reduction of paving materials could be explored through recycling mining by-products into different applications, which will preserve natural resources and decrease environmental issues. One possible approach is to reuse quarry dust and mining ore waste as precursors in geopolymer applications. geopolymers are mineral polymers rich in aluminosilicates with an amorphous to a semi-crystalline three-dimensional structure. The current review aims to summarize the studies conducted during the past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 121 publications
1
26
0
1
Order By: Relevance
“…The leaching conditions that yielded the optimum recovery of silica were then used to leach foundry sand to generate DFS for the development of geopolymers. It is reported that sodium is the better reagent for the preparation of geopolymers, as compared to potassium [28]. This is due to Na + cation being better in promoting alumino-silicates than K + cations [28].…”
Section: Method: Geopolymerization Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaching conditions that yielded the optimum recovery of silica were then used to leach foundry sand to generate DFS for the development of geopolymers. It is reported that sodium is the better reagent for the preparation of geopolymers, as compared to potassium [28]. This is due to Na + cation being better in promoting alumino-silicates than K + cations [28].…”
Section: Method: Geopolymerization Processmentioning
confidence: 99%
“…It is reported that sodium is the better reagent for the preparation of geopolymers, as compared to potassium [28]. This is due to Na + cation being better in promoting alumino-silicates than K + cations [28]. Geopolymers were developed by mixing DFS with NaOH solution as the alkaline activation reagent.…”
Section: Method: Geopolymerization Processmentioning
confidence: 99%
“…The reactive aluminosilicates in both the NMW and CFA may have been easily dissolved by the SH, so less of the hydroxide is needed before the geopolymerization process. Thus, SS is considerably needed as a binding source and promoter of hardening [38].…”
Section: Factors Affecting Compressive Strengthmentioning
confidence: 99%
“…This model indicates that the proper selection of precursors needs to be determined using characterization methods. Lastly, Ioptimal design of experiment can help us fine-tune the mix design of the geopolymer for the sampling and selection of a new precursor source [38]. The numerical optimization tool of the Design-Expert software was used to find the optimal point on the response surface to maximize the unconfined compressive strength of the synthesized geopolymer.…”
Section: Regression Modelmentioning
confidence: 99%
“…Quarry waste has been used in various applications such as geopolymer production [ 4 ], soil stabilization [ 5 ], pavements [ 6 , 7 ] and production of artificial aggregates [ 8 ]. Studies and experimental applications have also highlighted the possibility of using quarry waste in cementitious materials.…”
Section: Introductionmentioning
confidence: 99%